Strukturalne i programowe reformy polskiej oświaty w latach 1998–2017 na łamach tygodnika „Polityka” - Gołębiowski, Dariusz (Biuletyn Historii Wychowania, 2018)
A radical reform of the education system, one of the pillars of the four major reforms of Jerzy Buzek’s government, followed by a reform of the core curriculum by Minister Katarzyna Hall, and finally a controversial reform by Anna Zalewska under which some middle-level schools in operation since 1999 are being shut down are events covered in numerous publications, among them in leading opinion weeklies in Poland. One of such weeklies is “Polityka,” published continuously since 1957, where dozens of articles on education and reforms have been published over the last 20 years. The article is a concise analysis of the texts published in “Polityka”, the issues raised and the authors’ attitudes to the changes introduced in the subsequent years to the Polish education system.